Active penetration of Trypanosoma cruzi into host cells: historical considerations and current concepts - Carvalho, Tecia M.; De Souza, Wanderley (Frontiers in Immunology, 2013)
A significant number of scientific groups working on several countries have made efforts to better understand the process of invasion of several types of host cells by Trypanosoma cruzi, the etiologic agent of Chagas disease. In this mini-review we analyze the two mechanisms of invasion considered to be relevant: active penetration and endocytosis. The term active penetration is considered in view of its original description by Dvorak and co-workers. Taking into consideration all results obtained we conclude that endocytosis, with its many variations, is the only mechanism used by T. cruzi to invade host cells.